Infrared Spectroscopy Techniques in the Characterization of SOFC Functional Ceramics - Macedo, Daniel A.; Cesário, Moisés R.; Souza, Graziele L.; Cela, Beatriz; Paskocimas, Carlos A.; Martinelli, Antonio E.; Melo, Dulce M. A.; Nascimento, Rubens M. (IntechOpen, 2012)
None